Factors contributing to domestic violence among Latino male perpetrators - Gutierrez, Lisa (ProQuest Dissertations & Theses, 2010)
The purpose of this study was to examine the relationships among attitudes and beliefs towards domestic violence and acculturation strategy, ethnic identity, preferred language type (English, Spanish) and time spent (in weeks) in a court-mandated domestic violence offender process group among Latino men. The five subscales of the Inventory of Beliefs about Wife Beating (IBWB) measured attitudes and beliefs towards domestic violence. Acculturation was measured by the Acculturation Rating Scale for Mexican Americans-II (ARSMA-II) and ethnic identity was measured by the Multigroup Ethnic Identity Measure-Revised (MEIM-R). The total number of participants was 213, average age was 34.1 years old (SD = 10.18). Participants were given the option of taking the Spanish or English version of the questionnaire. Statistical analyses included two three-way between subjects multivariate analyses of variance with language type (English, Spanish) acculturation strategy (assimilated, traditional, bicultural, marginalized) or MEIM ethnic identity—exploration (high, low) and MEIM ethnic identity—commitment (high, low) as independent variables. The five subscales of the Inventory of Beliefs about Wife Beating served as five dependent variables including Wife Beating is Justified, Wives Gain from Beatings, Help Should be Given, Offender Should be Punished and Offender is Responsible. Amount of time in a process group served as a covariate. The results of this study showed that acculturation strategy did not have an impact on the participants' attitudes and beliefs towards domestic violence. However, this study did produce a significant effect regarding MEIM ethnic identity commitment and the Help Should be Given subscale on the IBWB. The covariate, treatment time did not significantly adjust the dependent measures. Implications of these results were discussed.